Uniconazole effect on endogenous hormones, proteins and proline contents of barley plants (Hordeum vulgare) under salinity stress (NaCl) - MOHAMED A. BAKHETA; MOHAMED M. HUSSEIN (Nusantara Bioscience, 2014)
Abstract. Bakheta MA, Hussein MM. 2014. Uniconazole effect on endogenous hormones, proteins and proline contents of barley plants (Hordeum vulgare) under salinity stress (NaCl). Nusantara Bioscience 6: 39-44. Pot experiments were carried out during two growth seasons 2010/2011 under greenhouse conditions of the National Research Centre, Dokki, Cairo, Egypt to investigate the response of barley plants (Hordeum vulgare L) grown under salinity stress (2500 or 5000 ppm) to spraying with solutions of uniconazole at 150 or 200 ppm. The obtained results showed that irrigation with saline solutions caused increases in the amounts of abscisic acid (ABA), crude protein, total soluble-protein, and proline contents. The results showed that spraying barley plants grown under saline solutions with uniconazole increased endogenous hormone contents of ABA, cytokinins, crude protein, total soluble protein, and proline but caused decreases in the amounts of endogenous indole acetic acid (IAA) and gibberellic acid (GA3). High protection of abscisic acid in treating plants with uniconazole and under salt stress (interaction effect) increases proline, proteins and soluble protein which has been proposed to act as compatible solutes that adjust the osmotic potential in the cytoplasm. Thus, these biochemical characters can be used as a metabolic marker in relation to salinity stress.